Lower extremities joint angles during squats - underexplored parameter of standard rehabilitation and sports exercise - Viktor Kotiuk; Oleksandr Kostrub; Roman Blonskyi; Lyudmyla Sushchenko; Dmitry Smirnov; Nazar Vadzyuk (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
The purpose was to specify the lower extremity joint angles in different squats for the future development of adequate computational models of the joints. Methods. We investigated joint angles in the lower extremity joints in 103 athletes in different types of squats with and without added weight (barbell) 75% of 1 repetition maximum. Results. The mean knee and hip flexion and ankle dorsiflexion angles in horizontal squats are respectively 113.42°, 128.21°, and 23.27°; in half-squats 70.60°, 87.94°, and 15.60°; in lunges 98.04°, 96.36°, and 8.02°; in Smith machine squats 94.42°, 106.28°, and 4.46°. In a horizontal squat with a barbell, the knee joint flexion and the ankle joint dorsiflexion angles are significantly larger (by 4.56 ° and 3.11 °, respectively) than in squats without added weight. The knee joint flexion and ankle dorsiflexion angles in lunges are significantly less in barbell squats (by 4.15° and 4.37°, respectively). The knee flexion angle in horizontal barbell squats in male athletes is significantly larger than in female athletes (by 4.71°). Conclusions. The mean knee and hip flexion and ankle dorsiflexion angles in different types of squats are established and may be used for further research. Horizontal squats produce greater lower extremity joint angles.